EBOLA HEMORRHAGIC FEVER: CLINICAL MANAGEMENT AND PREVENTION - Muhammad Aditya (Fakultas Kedokteran Universitas Lampung, 2014)
Ebola hemorrhagic fever is one of at least 30 known viruses capable of causing viral hemorrhagic fever syndrome. It is a severe, often fatal disease in humans and nonhuman primates (such as monkeys, gorillas, and chimpanzees). Ebola first appeared in 1976 in 2 simultaneous outbreaks, in Nzara, Sudan, and in Yambuku, Democratic Republic of Congo. The latter was in a village situated near the Ebola River, from which the disease takes its name. The current (2014) Ebola virus outbreak in West Africa has seized the world's attention, because this become the deadliest Ebola outbreak in recorded history and it is significant and primarily involves 4 African countries—Guinea, Liberia, Sierra Leone, and Nigeria. Besides the high mortality rate, the cure for Ebola disease has not been found yet. As of Augustus 31, 2014, 3.707 total suspected or confirmed cases (2.106 laboratory-confirmed) had been reported in these countries, resulting in 1.848 deaths. Based on genetic analysis, the virus is 97% identical to the Zaire ebolavirus identified in recent (earlier in 2014) cases in Gabon and the Democratic Republic of the Congo. Ebola disease management generally in the form of therapeutic support, relieve symptoms, and focus on the early identification of complications. Prognosis is poor, especially Ebolavirus Zaire strain, which has a case fatality rate of up to 89%. [JuKe Unila 2014; 4(8):245-253]